Neospora caninum Activates p38 MAPK as an Evasion Mechanism against Innate Immunity - Mota, Caroline M.; Oliveira, Ana C. M.; Davoli-Ferreira, Marcela; Silva, Murilo V.; Santiago, Fernanda M.; Nadipuram, Santhosh M.; Vashisht, Ajay A.; Wohlschlegel, James A.; Bradley, Peter J.; Silva, João S.; Mineo, José R.; Mineo, Tiago W. P. (Frontiers in Microbiology, 2016)
Due to the high prevalence and economic impact of neosporosis, the development of safe and effective vaccines and therapies against this parasite has been a priority in the field and is crucial to limit horizontal and vertical transmission in natural hosts. Limited data is available regarding factors that regulate the immune response against this parasite and such knowledge is essential in order to understand Neospora caninum induced pathogenesis. Mitogen-activated protein kinases (MAPKs) govern diverse cellular processes, including growth, differentiation, apoptosis, and immune-mediated responses. In that sense, our goal was to understand the role of MAPKs during the infection by N. caninum. We found that p38 phosphorylation was quickly triggered in macrophages stimulated by live tachyzoites and antigen extracts, while its chemical inhibition resulted in upregulation of IL-12p40 production and augmented B7/MHC expression. In vivo blockade of p38 resulted in an amplified production of cytokines, which preceded a reduction in latent parasite burden and enhanced survival against the infection. Additionally, the experiments indicate that the p38 activation is induced by a mechanism that depends on GPCR, PI3K and AKT signaling pathways, and that the phenomena here observed is distinct that those induced by Toxoplasma gondii’s GRA24 protein. Altogether, these results showed that N. caninum manipulates p38 phosphorylation in its favor, in order to downregulate the host’s innate immune responses. Additionally, those results infer that active interference in this signaling pathway may be useful for the development of a new therapeutic strategy against neosporosis.